Analisis dan Perancangan Aplikasi Inventori Berbasiskan Rfid Pada PT. ABC - Herwin, Herwin; Saputra, Richard (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this research is to reduce the damaged material, applying the concept of FIFO for retrieval of row materials, and accelerate the search and also to simplify the detection of raw materials. Software development method used involves three main parts namely the method of analysis, design and literature. Analysis methods including survey of the running system, an analysis of survey findings, identify information needs, identify system requirenments. The design method approach to Unified Modelling Language (UML). The results is an inventory application that uses Radio Frequency Identification (RFID) tags as a replacement label where RFID tags can store data. Conslusions from this research is minimizing the company’s financial losses due to storage of raw materials and minimizing time to search raw materials using RFID that also can provide actual and accurate information for the company.